2004
DOI: 10.1002/chin.200422080
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Nitrogen‐Heterocyclic Compounds Through Zirconium‐Mediated Intramolecular Alkene‐Carbonyl Coupling Reaction of N‐(o‐Alkenylaryl)carbamate Derivatives.

Abstract: Reactions of organo-metal compounds Reactions of organo-metal compounds O 0350Construction of Nitrogen-Heterocyclic Compounds Through Zirconium-Mediated Intramolecular Alkene-Carbonyl Coupling Reaction of N-(o-Alkenylaryl)carbamate Derivatives. -The outcome of the reaction between N-(o-alkenylaryl)carbamates and zirconocene complexes strongly depends on the nature of the N-substituent. Thus, N-benzyl derivatives undergo convenient ring closure to afford fused lactams. In contrast, starting from N-tosyl derivat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Of additional interest is that the majority of examples involving group 4 organometallic complexes require activation by the aluminum complex, methylalumoxane (MAO). In terms of other zirconocene complexes, Negishi and co-workers demonstrated that n Bu 2 ZrCp 2 was an effective isomerization catalyst of (2-deuterioallyl)­benzene, while Taguchi and researchers encountered isomerization of tert -butyl 2-allylphenyl­[(4-methylphenyl)­sulfonyl]­carbonate with the zirconium–butene complex prepared from Cp 2 ZrCl 2 and n butyllithium …”
Section: Transition Metal-mediated Isomerizations Of Allylbenzenesmentioning
confidence: 99%
See 1 more Smart Citation
“…Of additional interest is that the majority of examples involving group 4 organometallic complexes require activation by the aluminum complex, methylalumoxane (MAO). In terms of other zirconocene complexes, Negishi and co-workers demonstrated that n Bu 2 ZrCp 2 was an effective isomerization catalyst of (2-deuterioallyl)­benzene, while Taguchi and researchers encountered isomerization of tert -butyl 2-allylphenyl­[(4-methylphenyl)­sulfonyl]­carbonate with the zirconium–butene complex prepared from Cp 2 ZrCl 2 and n butyllithium …”
Section: Transition Metal-mediated Isomerizations Of Allylbenzenesmentioning
confidence: 99%
“…In terms of other zirconocene complexes, Negishi and co-workers demonstrated that n Bu 2 ZrCp 2 was an effective isomerization catalyst of (2-deuterioallyl)benzene, 804 while Taguchi and researchers encountered isomerization of tert-butyl 2allylphenyl[(4-methylphenyl)sulfonyl]carbonate with the zirconium−butene complex prepared from Cp 2 ZrCl 2 and n butyllithium. 805 Rao and Periasamy discovered that a mixture of Cp 2 TiCl 2 (20 mol %), Grignard-grade magnesium, and BrCH 2 CH 2 Br facilitated the double bond rearrangement of allylbenzene 3 and safrole 6 into the respective trans products 4 and 19 in yields of 77% and 80% (Scheme 164). 806 Of importance here is that these conditions have the added advantage of being effective at room temperature and that isomerizations were complete within 2 h. In a subsequent publication, the authors postulated that under the reaction conditions a titanocene−ethylene complex and/or a titanium hydride species could be the agents responsible for the observed isomerization process.…”
Section: Cobalt-catalyzed Isomerizationsmentioning
confidence: 99%